Caracterização de micro-bacia hidrográfica experimental no semi-árido brasileiro como suporte a estudos de degradação - Alves, Nilvia Nara de Lucena (2008)
This work aims to present an analysis through the experiments driven in a watershed to support the future studies that point out to identification and checking the causes that promote the degradation in the semiarid region of the Northeast of Brazil. It was taken two watershed cited in the Escola Agrotécnica Federal de Iguatu – EAFIGT located in the Iguatu County, Ceará, Brazil, It was made the morphometrical characterization, the identification of the vegetation (herbaceous and arboreal) substrates and the evaluation of the sediments transport related to physical aspects with the hydrological processes. The experiment was developed during the first semester of 2008 (rainfall station). The considered morphometrical aspects were: length and sinuosity of the main stream and slope, area, length, form factor, compactness coefficient, concentration time of the watershed, as well as the runoff time. The cover vegetation was estimated account all species present in a sampled space of 10 m x 10 m in a randomized design with three replications in each watershed. From the all computed individuals present in each sampled space, the density of vegetable was obtained by area and the population was estimated in the watersheds. In the evaluation of the sediments transport it was used the following equipments: suspended sediment flow collectors, weir parshall and meteorological station. The station was made in the Universidade Federal do Ceará- UFC/DENA/LEMA. Results showed that cover vegetation was composed, basically by 23 species, being the most abundant Hyptis sauaviolens (L.) point (Bambural) and Hyptis sp. (Melosa) herbaceous and arboreal shrubby the Aspidosperma pyrifolium Mart (Pereiro). The plant density for unity of area was 1,43 individual/m2 and 1,18 individual/m2 for the watershed B1 and B2, respectively. The estimated of vegetation population was 16,395 individuals for B1 and 24,421 individuals for B2, respectively. During the studied period, the air temperature went from 41 oC to 20 oC and the relative humidity went from 100% to 35%. The most intensity rainfall for 5 minutes was 140 mm h-1 in an event of 126 mm. The watershed areas were 1,15 ha and 2,06 ha for the watershed B1 and B2, respectively, with slope 8,7 for B1 and 10,6 %. for B2. The sinuosity of streams were 1,2 for the B1 and 1,4 for B2. The sediment delivery during the collected period was 9,22 and 17,95 kg for watersheds B1 and B2, respectely. The peak of flow registered in the B2 watershed was 740 m3 h-1 while in the B1 watershed was not possible register the peak flow. In spite of the experimental area present a good cover vegetable, it was identified the human activity. Although the number of vegetable species is high, it points out to succession stage. Even with the same characteristic pair watersheds can have different hydrologic behavior.